Indicador de probabilidade de ocorrência de irregularidades: proposta de um modelo à auditoria pública federal - Julio Cesar Silveira (2011)
This research aimed to present a model to replace another one used by Controladoria Geral da União (CGU), (Union General Comptroller - UGC) called Sorteio Público (Public Lottery), in order to direct the audit of that agency to municipalities with the greatest probability of irregularities occurrence on funds management transferred by Confederacy. To this objective, we performed a descriptive research, using as database the audit reports released by UGC, from 2003 to 2010. The sample consisted of 202 reports from municipalities audited by UGC. We sought to demonstrate the relationships between the variable dependent "Detecting Irregularities (Detec)" and a set of nine explanatory variables for this phenomenon, according to Albuquerque and Ramos (2006) and Weber (2006) studies. For data analysis, Logit regression technique was used. According to research results, we found a model containing four variables statistically significant capable to detect, within probabilistic criteria, possible irregularities managed by mayors of funds transferred by Union to their respective municipalities, helping UGC auditors to plan their work. It was also found that the proposed model to UGC had a level of accuracy greater than 80%. We conclude therefore, by the results presented in this research, that it was possible to achieve the proposed goal, submiting to Union General Comptroller (UGC) a new methodology by a model to be used in the audit planning, replacing the criterion of public lottery. It is noteworthy that the results presented in this study are not conclusive, but allow inferences about a relatively unexplored subject by Brazilian Academy, especially in Accounting.